Strategi Lembaga Penyiaran Publik (LPP) Radio Republik Indonesia (RRI) Padang Untuk Mempertahankan Minat Pendengar di Era Digitalisasi Penyiaran - Latifa Hannum Siregar; Vira Farisa Risman; Rizki Syafril (Jurnal Relasi Publik, 2024)
The aim of this research is to find out and describe RRI's reporting approach so that listeners remain interested in the era of digital broadcasting. Qualitative descriptive methodology is used in this research methodology. This research aims to discuss RRI's reporting strategy regarding Human Resources, Broadcast Hours, Target Audience, and Content. Data collection methods include documentation, library research, interviews, and observation. Based on research, RRI uses the following tactics to maintain listener interest: (1) developing listener-involving programs where listeners can convey and share information with the public, which is sometimes known as citizen journalism. (2), RRI broadcasts all day, every day. (3) RRI and Pusdiklat work together to produce featured reporter and presenter programs, as well as holding regular conversations with reporters and presenters in the field. The aim of this exercise is to improve the quality of reporters and presenters, whose job is to involve the audience directly. Apart from that, technology will also enter the digital era. (4) RRI developed three programs RRI Play, Be Young, and RRI 30 Seconds which are available for download from the Google Store and Appstore. This application is based on the Android and iOS operating systems.